The overview effect and nature-relatedness - McKeever, Niall; Nezami, Annahita; Kourtis, Dimitrios (Frontiers in Virtual Reality, 2024)
Climate scientists increasingly agree that human behavior significantly contributes to global warming and biodiversity decline. Recent research emphasizes the importance of "human-nature connectedness" (HNC) as a reliable predictor of psychological well-being and increased engagement in proenvironmental behavior (PEB). While evidence supports a positive correlation between HNC and PEB, establishing causation remains elusive. Nevertheless, exploring this link is crucial, given its potential to enhance pro-environmental behavior. Considering the complex interplay of factors influencing PEB, developing effective interventions in this area requires a deeper understanding of the psychological and emotional processes involved. Armed with this understanding, stakeholders can design and implement successful sustainability interventions that promote well-being on individual, collective, and planetary levels.One psychological phenomenon believed to have a strong effect on HNC and PEB is "The Overview Effect," a term used to describe the shift in awareness some astronauts experience when viewing Earth from outside its atmosphere. This pilot study explored whether a 360 virtual reality Overview Effect (VROE) experience created by EarthscapeVR® influences human-nature connectedness and whether a correlation exists between participants' average HNC scores and openness to experience scores. 60 student participants took part in the study. The results showed significant increases in questionnaire reports on HNC (p <0.0021) in the experimental condition (VROE condition) compared to the control group (p = 0.97), with no correlation (r = 0.137) between participants' average HNC scores and openness to experience scores. While these results are not conclusive and further research is necessary, the initial findings support translating the Overview Effect into virtual reality to enhance human-nature connectedness.